Arthur J. Morris papers - Morris, Arthur J., 1881-1973.
Correspondence, oral history interview transcript, speeches and writings, notes, subject files, newspaper clippings, printed material, and other papers documenting Morris's involvement in the development of consumer credit in the American banking industry. Subject files include financial statements, operation manuals, and printed material relating to the Morris financial empire which included the Financial General Corporation, the Industrial Acceptance Corporation, the Industrial Finance Corporation, the Morris plan banks, the Morris Plan Corporation of America, and the Morris Plan Insurance Society. Includes Morris's notes (circa 1901) as a law student at the University of Virginia.
Library of Congress Prints and Photographs Division.
Library of Congress Motion Picture, Broadcasting, and Recorded Sound Division.
Banker and lawyer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Financial General Corporation; Industrial Acceptance Corporation; Industrial Finance Corporation; Morris Plan Corporation of America; Morris Plan Insurance Society; University of Virginia -- Students; Banks and banking -- United States; Consumer credit -- United States; Credit -- United States; Universities and colleges -- Virginia -- Charlottesville; Bankers; Lawyers